Formation of graphitic films on Cu(111) via electron beam induced deposition. (January 2021) - Bonetto, F.; Silva, C.; Ferreira, E.H. Martins; Candia, A.; Passeggi, M.C.G.; Montoro, S.; Vidal, R.
Abstract: Electron beam induced deposition using ethylene as precursor gas is used to generate carbonaceous films on Cu(111). The study was performed in an ultrahigh vacuum chamber for two different precursor gas pressures, and two substrate temperatures. Auger electron spectroscopy and reflection electron energy loss spectroscopy were used to characterize the film growth process in-situ. These techniques allowed us to determine how the deposited film covers the Cu(111) substrate as a function of the ethylene exposure, obtaining a final coverage of up to 0.8 monolayer, depending on the growing conditions. Based on the CKLL Auger line shape and on the reflection electron energy loss (REELS) spectra we can conclude on the graphitic characteristics of the grown film and on the optimum growing conditions: lower substrate temperature and higher ethylene pressure. Raman spectroscopy and scanning tunneling spectroscopy were used as ex-situ techniques to assess the properties of the grown film. Results from both techniques indicate that the film consists of small (10–20 nm in size) nanocrystals of few (1–2) layers graphene. Once optimized, this method may allow growing graphene with a predesigned pattern, without the need to heat the substrate at high temperatures. Highlights: Carbon films can be grown on Cu via electron irradiation in an ethylene atmosphere. Auger and energy-loss spectroscopy reveal graphitic characteristics of grown films. Raman and STM show the grown films are 10–20 nm patches of few layers graphene. The method may allow growing graphene without the need of heating the substrate.